2013
DOI: 10.3748/wjg.v19.i23.3596
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for colonoscopic perforation: A population-based study of 80118 cases

Abstract: The cumulative 7 d incidence of colonic perforation in this cohort was 0.06%. Advanced age and female gender were significantly more likely to have perforation. Increasing albumin and BMI resulted in decreased risk of colonic perforation. Having a colonoscopy indication of abdominal pain or Crohn's disease resulted in a higher risk of colonic perforation. Colonoscopies performed in inpatients and particularly the ICU setting had substantially greater odds of perforation. Biopsy and polypectomy did not increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…Fourteen studies were retrospective ( 4,7,8,(10)(11)(12)14,15,17,19,21,22,24,25 ) and seven were prospective studies ( 5,6,9,13,16,18,20 ). Th ere were four studies from the United States ( 5,12,17,22 ), three from Canada ( 15,20,21 ), ten from Europe (6)(7)(8)(9)(10)(11)13,16,18,19 ), three from South-Korea ( 14,24,25 ), and one from New Zealand ( 4 ). Mean age of the study populations varied from 50.4 to 70.0 years ( 4,6,10,14-21,24,25 ) (median age, 57 to 75 years ( 5,9,13,16,21 )); 51.5% were males (4)(5)(6)…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Fourteen studies were retrospective ( 4,7,8,(10)(11)(12)14,15,17,19,21,22,24,25 ) and seven were prospective studies ( 5,6,9,13,16,18,20 ). Th ere were four studies from the United States ( 5,12,17,22 ), three from Canada ( 15,20,21 ), ten from Europe (6)(7)(8)(9)(10)(11)13,16,18,19 ), three from South-Korea ( 14,24,25 ), and one from New Zealand ( 4 ). Mean age of the study populations varied from 50.4 to 70.0 years ( 4,6,10,14-21,24,25 ) (median age, 57 to 75 years ( 5,9,13,16,21 )); 51.5% were males (4)(5)(6)…”
Section: Resultsmentioning
confidence: 97%
“…Post-colonoscopy "perforation" rate ranges from 0 to 1.7/1,000 colonoscopies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), post-colonoscopy "bleeding" rate from 0 to 22.3/1,000 colonoscopies ( 4-11,13-18, 20-22,24,25 ), and "mortality" rate from 0 to 2.0/1,000 colonoscopies (4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)25 ). In screening populations, an overall postcolonoscopy complication rate of 2.8/1,000 procedures has been reported ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that patients over 65 years of age present significant risks for perforation (1,(21)(22)(23). In some studies, it has been reported that the perforation rate in patients over 75 years of age can increase by four to six times compared to that in young patients (24,25 (24) observed that the perforation rate is higher in patients with two or more comorbidities.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, increased risk of colonic perforation was observed in patients with ASA scores greater than 3. Handami et al (21) reported older age, female gender, low BMI, co-existent diseases, and low albumen levels as risk factors of increased perforation rates in hospitalized patients, especially among those admitted to the intensive care unit. In terms of indications, perforation rates have been found to be higher during procedures performed for diagnosing abdominal pain, anemia, Crohn's disease, and bleeding (21).…”
Section: Discussionmentioning
confidence: 99%
“…In a large study in 2013 performed by Hamadani et al risk of colon perforation was about 1% in all colonoscopic studies (18). With the aid of a laparoscopic endoscopic hybrid approach, any full thickness colon wall injury due to thermal injuries, barotrauma or endoscope itself will be diagnosed properly and repaired if needed.…”
Section: Complicationsmentioning
confidence: 99%